Neumonía en niños menores de 5 años que acuden al hospital Julius Dopfner del cantón Zamora, año 2015 - Sarmiento Gòmez, Mayeny Alexandra (2016)
This study was conducted in order to determine the prevalence of pneumonia in children under 5 who come to the Canton Hospital Julius Doepfner Zamora, 2015. The methodology used for the study was retrospective, descriptive, cross-sectional field and bibliographic. For the collection of information proceeded to apply the technique of direct observation with the observation guide instrument 87 children who were hospitalized in pediatrics, which allowed us to determine the prevalence of 22.89% children who had pneumonia, in terms of sociodemographic characteristics age 1-3 years are more susceptible to pneumonia with 44.83%; the male with 56.33%; by ethnicity it predominates mixed with 90.82%; internal rural prevails with 56.32% and within the precipitating causes are: environmental with 41.72% were exposed to sudden temperature changes in the socio-economic are the economic level with 77.01% ; in nutritional formula feeding they are with 36.60% and 50.00% social was to be in contact with people with respiratory symptoms. Based on these results the author implemented a plan of action based on the same educational activities consisting of theoretical training and delivery of information material and home to the most vulnerable places visits took place. Concluding that the prevalence of pneumonia in children under 5 years is 22.89% and the main causes are sudden changes in temperature, low economic status, formula feeding and contact with people with respiratory symptoms Keywords: Pneumonia, Children under 5 years, Hospital.